2014
DOI: 10.1097/ccm.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Inhaled Nitric Oxide for the Treatment of Microcirculatory Dysfunction in Patients With Sepsis*

Abstract: Following macrocirculatory optimization, inhaled nitric oxide at 40 ppm did not augment microcirculatory perfusion in patients with sepsis. Further, we found no association between microcirculatory perfusion and multiple organ dysfunction after initial resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 63 publications
1
33
1
2
Order By: Relevance
“…Unfortunately, NO signaling is highly complex, with context-specific functions that can be both homeostatic and pathologic 5456 . Human studies of NO-targeted microvascular therapeutics have accordingly been disappointing 57,58 , potentially reflecting broad, nonspecific effects of NO manipulation 59 . These challenges (and opportunities) of NO-based therapies have been reviewed in detail elsewhere 60 .…”
Section: Pathogenesis Of Microvascular Dysfunction During Sepsismentioning
confidence: 99%
“…Unfortunately, NO signaling is highly complex, with context-specific functions that can be both homeostatic and pathologic 5456 . Human studies of NO-targeted microvascular therapeutics have accordingly been disappointing 57,58 , potentially reflecting broad, nonspecific effects of NO manipulation 59 . These challenges (and opportunities) of NO-based therapies have been reviewed in detail elsewhere 60 .…”
Section: Pathogenesis Of Microvascular Dysfunction During Sepsismentioning
confidence: 99%
“…(46) To date, there have been 2 randomized clinical trials in adults of inhaled nitric oxide for the treatment of existing microcirculatory disease. (47) (48) In both adult studies, no difference between the treatment and control arms was reported. In addition, none of the inhaled nitric oxidebronchopulmonary dysplasia prophylaxis, randomized clinical trials found any effect on the risk of periventricular leukomalacia, intraventricular hemorrhage, NEC, or longterm neurodevelopmental outcome.…”
Section: Can the Effect Of Hypoxic Vasodilation Be Augmented?mentioning
confidence: 79%
“…However, this strategy did not improve the sublingual microcirculation or organ function in a recent series of septic shock patients [49]. Of note, inhaled NO has major biological effects in the pulmonary network but only marginally increases plasma NO 2 - levels (up to 0.41 µ M , while normal values range between 0.05 and 0.30 µ M [20]) for use in peripheral hypoxic regions.…”
Section: Discussionmentioning
confidence: 99%